2017
DOI: 10.1111/bjc.12137
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver criticism, help‐giving, and the burden of schizophrenia among Mexican American families

Abstract: Objectives The present study tested an attribution model of help-giving in family caregivers of persons with schizophrenia as it relates to caregivers’ reported burden. We hypothesized (a) that caregivers’ attributions of their ill relatives’ responsibility for their symptoms would be associated with more negative and less positive affective reactions, (b) that affective reactions would be related to perceptions of administered support, and (c) that support would in turn predict greater burden. Methods We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…More criticism may be associated with greater burden. This is in consistent with Bianca T. Villalobos, et al 2017, who stated that their findings demonstrated that the high emotional expression or criticism link with caregiver burden [29].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More criticism may be associated with greater burden. This is in consistent with Bianca T. Villalobos, et al 2017, who stated that their findings demonstrated that the high emotional expression or criticism link with caregiver burden [29].…”
Section: Discussionsupporting
confidence: 88%
“…The emotion expression of the patients' relative is closely related to burden of disease. More negative affect is associated with less helping and more positive affect is associated with more helping and in turn greater helping would be associated with greater caregiver burden [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The disabling effect of schizophrenia not only affects individuals but also affects their families and health practitioners. The burden on families stems from monitoring the patient’s hygiene, the use of medication, comportment at social gatherings, follow-up with health care providers, and the need to deal with mood, cognitive and behavioural changes [ 11 13 ]. The burden of care on families with schizophrenia causes emotional distress in family members and increases their chances of also developing schizophrenia or other forms of mental illness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disabling effect of schizophrenia not only affects individuals but also affects their families and health practitioners. The burden on families stems from monitoring: the personal hygiene of the patient, the use of medication, comportment at social gatherings, follow-up with health care providers, and the need to deal with mood, cognitive and behavioural changes 16,17,18 . The burden of care on families with mental illness causes emotional distress in family members and increases their chances of also developing mental illness 19 .…”
Section: Introductionmentioning
confidence: 99%